Green paper on public sector reform (Office of Public Sector Reform CastriesLC, 1999)
Identifies some of the problems confronting the efficiency and effectiveness of the public service, and the strength of the public service. Discusses the implication of these issues. Recommends strategies for reducing these problems and taking the reform efforts forward.
Keywords: PUBLIC SECTOR